2005
DOI: 10.1007/s00415-005-0864-2
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of cerebral morphological changes in Parkinson's disease with and without dementia

Abstract: VBM revealed a significant loss of grey matter volume in PD patients with and without dementia with disease progression. The decrease in limbic and paralimbic regions is widespread in non-demented patients. Neocortical volume reduction is the most relevant finding in patients with dementia. This suggests that the neocortex is a substrate for dementia in Parkinson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 48 publications
5
77
1
Order By: Relevance
“…Lotze et al112 have shown that the less dopamine transporter availability (DAT) present in the putamen, the lower the ventrolateral prefrontal cortex activation in response to emotional gestures and highlighted a positive correlation between the putaminal DAT reduction and the number of errors in emotional gestures recognition. Similarly, morphometry analyses reported decreased gray‐matter volume in numerous limbic, paralimbic, and neocortical associative temporo‐occipital areas64, 66, 113, 114 and showed that the atrophy could be associated with the deficit, as gray‐matter volume in these regions correlated with patients' FER performance 64, 66. More specifically, impairment of the amygdala, observed since the early stages and worsening with disease progression,107, 115, 116 has often been invoked to explain emotional deficiencies in PD, as we know that the amygdala circuitry is involved in multiple behavioral functions including emotional arousal and emotion‐saliency appraisal 117, 118.…”
Section: Discussionmentioning
confidence: 84%
“…Lotze et al112 have shown that the less dopamine transporter availability (DAT) present in the putamen, the lower the ventrolateral prefrontal cortex activation in response to emotional gestures and highlighted a positive correlation between the putaminal DAT reduction and the number of errors in emotional gestures recognition. Similarly, morphometry analyses reported decreased gray‐matter volume in numerous limbic, paralimbic, and neocortical associative temporo‐occipital areas64, 66, 113, 114 and showed that the atrophy could be associated with the deficit, as gray‐matter volume in these regions correlated with patients' FER performance 64, 66. More specifically, impairment of the amygdala, observed since the early stages and worsening with disease progression,107, 115, 116 has often been invoked to explain emotional deficiencies in PD, as we know that the amygdala circuitry is involved in multiple behavioral functions including emotional arousal and emotion‐saliency appraisal 117, 118.…”
Section: Discussionmentioning
confidence: 84%
“…One longitudinal study showed a progressive gray matter volume (GMV) decrease in patients with PD with and without dementia with disease progression during a mean follow-up period of 25 months. 15 In that study, a progressive GMV decrease in the limbic/paralimbic and temporo-occipital regions was observed in patients with PD, while in patients with dementia, the loss mainly involved the neocortical regions. However, in that study, no healthy matched controls were included.…”
mentioning
confidence: 71%
“…On the one hand, those ROIs based on the results in the present study were defined by cluster-based method-that is, clusters that showed significant differences in the contrasts of [(PD1 ϩ Control1) Ͼ (PD2 ϩ Control2)] (bilateral caudate body; MNI coordinates: Ϫ8, 3, 18; 9, 5, 18) and [(PD2 Ͼ PD1) Ͼ (Control2 Ͼ Control1)] (left thalamus; MNI coordinates: Ϫ21, Ϫ24, 3) were defined as ROIs by using xjView software (http://www.alivelearn.net/xjview). On the other hand, to compare with the previous longitudinal study, 15 we defined additional ROIs on the basis of a sphere with a radius of 6 mm centered at the anterior cingulate cortex (MNI coordinates: 1, 31 19), posterior cingulate cortex (MNI coordinates: 11, Ϫ49, 30), hippocampus (MNI coordinates: Ϫ22, Ϫ19, Ϫ11), and hypothalamus (MNI coordinates: 1, Ϫ9, Ϫ5) by using WFU_PickAtlas software (http:// software.incf.org/software/wfu_pickatlas/ download). For each subject at a single time point (baseline and follow-up), the GMV in each ROI was computed by the sum of the volume of each voxel in the ROI.…”
Section: Roi Analysismentioning
confidence: 99%
“…MRI-based voxel-based morphometry (VBM) offers an operator-independent, unbiased and comprehensive morphological analysis of the brain. VBM has shown more widespread loss of grey matter in PD with dementia (PDD) [8,9,50,56,62]. VBM may also allow to distinguish PD from atypical Parkinsonian disorders [7,55].…”
Section: Introductionmentioning
confidence: 99%